New bounds for Laplacian energy - Gutman, Ivan (Vojnotehnički glasnik / Military Technical Courier, 2019)
Introduction/purpose: The Laplacian energy (LE) is the sum of absolute values of the terms μi-2m/n, where μi , i=1,2,…,n, are the eigenvalues of the Laplacian matrix of the graph G with n vertices and m edges. The basic results of the theory of LE are outlined, and some new obtained. Methods: Spectral theory of Laplacian matrices is applied. Results: A new class of lower bounds for LE is derived. Conclusion: The paper contributes to the Laplacian spectral theory and tp the theory of graph energies.
Keywords: spectral graph theory; Laplacian spectrum (of graph); Laplacian energy